GITR differentially affects lung effector T cell subpopulations during influenza virus infection. Issue 6 (3rd March 2020) - Chu, Kuan-Lun; Batista, Nathalia V.; Girard, Mélanie; Law, Jaclyn C.; Watts, Tania H.
Abstract: Tissue resident memory T cells (Trm) are critical for local protection against reinfection. The accumulation of T cells in the tissues requires a post-priming signal from TNFR superfamily members, referred to as signal 4. Glucocorticoid-induced TNFR-related protein (GITR; TNFRSF18) signaling is important for this post-priming signal and for Trm formation during respiratory infection with influenza virus. As GITR signaling impacts both effector T cell accumulation and Trm formation, we asked if GITR differentially affects subsets of effector cells with different memory potential. Effector CD4 + T cells can be subdivided into 2 populations based on expression of lymphocyte antigen 6C (Ly6C), whereas effector CD8 + cells can be divided into 3 populations based on Ly6C and CX3CR1. The Ly6C hi and CX3CR1 hi T cell populations represent the most differentiated effector T cells. Upon transfer, the Ly6C lo CD4 + effector T cells preferentially enter the lung parenchyma, compared to the Ly6C hi CD4 + T cells. We show that GITR had a similar effect on the accumulation of both the Ly6C hi and Ly6C lo CD4 + T cell subsets. In contrast, whereas GITR increased the accumulation of all three CD8 + T cell subsets defined by CX3CR1 and Ly6C expression, it had a more substantial effect on the least differentiated Ly6C lo CX3CR1 lo subset. Moreover, GITR selectively up-regulated CXCR6 on the less differentiated CX3CR1 lo CD8 + T cell subsets and induced a small but significant increase in CD127 selectively on the Ly6C lo CD4 + T cell subset. Thus, GITR contributes to accumulation of both differentiated effector cells as well as memory precursors, but with some differences between subsets.